Multiple myeloma: ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up - Moreau, Philippe; Goldschmidt, Hartmut (Annals of oncology, 2017)
Multiple myeloma (MM) accounts for 1% of all cancers and ∼ 10% of all haematological malignancies. The incidence in Europe is 4.5-6.0/100 000/year with a median